Practical permeability-based hepatic clearance classification system (HepCCS) in drug discovery. (December 2014) - Fan, Peter W; Song, Yang; Berezhkovskiy, Leonid M; Cheong, Jonathan; Plise, Emile G; Khojasteh, S Cyrus
Background: The use of liver microsomes and hepatocytes to predict total in vivo clearance is standard practice in the pharmaceutical industry; however, metabolic stability data alone cannot always predict in vivo clearance accurately.Results: Apparent permeability generated from Mardin–Darby canine kidney cells and rat hepatocyte uptake for 33 discovery compounds were obtained.Conclusion: When there is underprediction of in vivo clearance, compounds with low apparent permeability (less than 3 × 10 -6 cm/s) all exhibited hepatic uptake. A systematic approach in the form of a classification system (hepatic clearance classification system) and decision tree that will help drug discovery scientists understand in vitro–in vivo clearance prediction disconnect early is proposed.